Oncogenic Roles of Small Nucleolar RNA Host Gene 7 (SNHG7) Long Noncoding RNA in Human Cancers and Potentials - Najafi, Sajad; Ghafouri-Fard, Soudeh; Hussen, Bashdar Mahmud; Jamal, Hazha Hadayat; Taheri, Mohammad; Hallajnejad, Mohammad (Frontiers in Cell and Developmental Biology, 2022)
Long non-coding RNAs are a class of non-coding transcripts characterized with more than 200 nucleotides length. Unlike their names, some short open reading frames (ORFs) have been recognized for them encoding small proteins. LncRNAs have been found to play regulatory roles in essential cellular processes like cell growth and apoptosis. Therefore, an increasing number of lncRNAs are identified with dysregulation in a wide variety of human cancers. SNHG7 is a lncRNA with upregulation in cancer cells and tissues. It is frequently reported with potency of promoting malignant cell behaviors in vitro and in vivo. Like oncogenic/ tumor suppressor lncRNAs, SNHG7 has been found to exert its tumorigenic functions through interaction with other biological substances. These include sponging target miRNAs (various number are identified), regulation of several signaling pathways, transcription factors, and effector proteins. Importantly, clinical studies demonstrate association between high SNHG7 expression and clinicopathological features in cancerous patients, worse prognosis, and enhanced chemoresistance. In this review, we have summarized recent studies in three eras of cell, animal, and human experiments to bold the prognostic, diagnostic, and therapeutic potentials.